Research Progress on Extraction of Cinnamon Essential Oil and the Mechanisms of Biological Activities - Yuhua HUANG; Mengmeng ZHANG; Xuan XIN; Weidong BAI; Wei WANG; Wenbin REN; Wenhong ZHAO; Shanghua YANG (Shipin gongye ke-ji)
Cinnamon essential oil is a kind of volatile oil extracted from cinnamon, which is composed of aldehydes, esters, and olefins. Knowns for its distinct aroma, cinnamon essential oil exhibits numerous biological activities, such as antioxidant, anti-inflammatory, anti-tumor and regulation of glucose and lipid metabolism-regulating effects. It has shown great application value in the fields of food and medicine. In recent years, researchers have developed various methods for extracting cinnamon essential oil. However, there is currently a lack of systematic understanding of the differences in substance types and contents of cinnamon essential oils prepared by different extraction methods. In addition, although the various functional activities and mechanisms of cinnamon essential oil have been widely reported, due to the fact that it is a mixture, the material basis for the its functional activities is not fully understood. This article systematically reviews the different extraction methods and composition of cinnamon essential oil in recent years, and summarizes the material basis and mechanism of action for its antioxidant, anti-inflammatory and other activities. This article aims to further promote the improvement and application of cinnamon essential oil extraction methods, deepen the understanding of the functional activities of cinnamon essential oil, and provide a reference for the rational development and utilization of cinnamon essential oil resources.